PENGEMBANGAN MODUL TERAPI AL-QUR’AN SURAH ALHUJURAT AYAT 11-13 UNTUK MENURUNKAN PRASANGKA SOSIAL - Berlianti, Reghina; Saam, Zulfan; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Modules are printed teaching materials designed for students tostudy independently. These media are often called independent teaching materials.Teachers do not teach or teach their students directly, but this module is sufficient. Thepurpose of this study is to find out the developmental procedure and results of thevalidity of the Quranic therapeutic module of surah Al-Hujurat Ayat 11-13 to reducesocial prejudice. This research is Research and Development (R&D) research which isa method of research and development can be defined as a scientific way to research,plan, produce and test the validity of the product that has been produced. After goingthrough the stages of study and analysis and review, the validity of the development ofthe Quran therapy module Surah Al-Hujurat Ayat 11-13 to reduce social prejudice isdivided into five aspects of evaluation, namely physical / appearance, introductoryaspects, content aspects, task aspects, summary aspects. Based on the evaluation resultsof the learning module qualification material achieved an average score of 84.25%. Itcan be interpreted that the confirmation states the development of the Quran therapymodule surah Al-Hujurat verses 11-13 to lower social prejudice into categories is verysuitable to be used as a medium of learningKey Words: Modules, Quranic Therapy, Social Prejudice